Utility of [18F] Fluoro-Deoxyglucose Positron Emission Tomography/Computed Tomography for Staging and Therapy Response Evaluation in Pediatric Rhabdomyosarcoma: A Case Series and Literature Review - Sa, Ri; Liu, Danyan; Zhao, Hongguang; Hou, Sen; Lin, Qiuyu; Guan, Feng (Frontiers in Medicine, 2020)
Abstract Background: The role of [18F] fluoro-deoxyglucose ([18F] FDG) positron emission tomography (PET/CT) in pediatric rhabdomyosarcoma (RMS) is not well established. This manuscript explores the role of staging and therapy response evaluation of PET/CT in a series of patients with RMS. Methods: Thirteen consecutive patients with pathologically proven RMS underwent baseline PET/CT scan and the second PET/CT for evaluation of therapy response, and maximum standard uptake value (SUVmax), mean standard uptake value (SUVmean), highest standardized uptake peak value (SUVpeak), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were obtained from baseline PET/CT and were used as potential predictors for evaluation of metabolic treatment response. Results: On baseline PET/CT, most RMS located in pelvic cavity, and upper arms ranked secondly. The primary lesions were large and showed invasion to the surrounding tissues. Lymph node metastases were seen in eight patients and eight patients showed distant metastatic to lung, liver and bone. The median SUVmax, SUVmean, SUVpeak of primary sites were 7.1, 4.0, and 5.9 respectively. The median MTV and TLG were 196.6 cm3, and 780.2, respectively. After therapy, six patients received complete metabolic response (CMR) and non-CMR occurred in seven patients on the second PET/CT. SUVmax, SUVpeak, MTV and TLG in patients with CMR were significantly lower than those in patients with non-CMR. Conclusions: Primary sites and metastatic lesions of RMS demonstrates increased glycolytic activity, which may allow them to be imaged using [18F] FDG PET/CT. Metabolic parameters derived from the baseline PET/CT have potential value for predicting CMR to therapy in pediatric RMS.